2017
DOI: 10.1089/mdr.2016.0100
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antimicrobial Efficacy of Tobramycin Against Staphylococcus aureus Biofilms in Combination With or Without DNase I and/or Dispersin B: A Preliminary Investigation

Abstract: Staphylococcus aureus in biofilms is highly resistant to the treatment with antibiotics, to which the planktonic cells are susceptible. This is likely to be due to the biofilm creating a protective barrier that prevents antibiotics from accessing the live pathogens buried in the biofilm. S. aureus biofilms consist of an extracellular matrix comprising, but not limited to, extracellular bacterial DNA (eDNA) and poly-β-1, 6-N-acetyl-d-glucosamine (PNAG). Our study revealed that despite inferiority of dispersin B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 28 publications
2
32
0
2
Order By: Relevance
“…Regarding the relative potency, we noticed that a reduction of 33% of metabolic activity or of 1 log 10 CFU was rarely reached in ASM and at drug concentrations that were higher than those in TGN or than the MIC measured for planktonic cultures. Although these effects do not strictly correspond to bacteriostasis, our results confirm that higher concentrations of antibiotics are needed to act against biofilms than against planktonic cultures (14,18,(22)(23)(24)(31)(32)(33)(34)(35). The low penetration and/or bioavailability of antibiotics in the biofilm matrix is probably a main reason for this loss in potency (3,4,18) and may become even more critical in ASM.…”
Section: Discussionmentioning
confidence: 54%
“…Regarding the relative potency, we noticed that a reduction of 33% of metabolic activity or of 1 log 10 CFU was rarely reached in ASM and at drug concentrations that were higher than those in TGN or than the MIC measured for planktonic cultures. Although these effects do not strictly correspond to bacteriostasis, our results confirm that higher concentrations of antibiotics are needed to act against biofilms than against planktonic cultures (14,18,(22)(23)(24)(31)(32)(33)(34)(35). The low penetration and/or bioavailability of antibiotics in the biofilm matrix is probably a main reason for this loss in potency (3,4,18) and may become even more critical in ASM.…”
Section: Discussionmentioning
confidence: 54%
“…In addition, we also showed that Lp.LTA induced bacterial dispersion from pre-formed biofilm of S. aueus . Biofilm dispersing agents, such as Dispersin B, chitosan, and glycoside hydrolases, have been reported to release planktonic cells that are more susceptible to antibiotics than bacterial cells shielded by biofilm ( Orgaz et al, 2011 ; Fleming et al, 2017 ; Waryah et al, 2017 ). Therefore, Lp.LTA may also act as a dispersing agent to potentiate antibiotic activity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one recent study showed that a combination of DNase I and dispersin B was significantly less effective in enhancing the antimicrobial efficacy of tobramycin against S . aureus than the individual enzymes alone [ 43 ]. However, a combination of DNase I and dispersin B did exhibit additive biofilm inhibiting activity against S .…”
Section: Discussionmentioning
confidence: 99%